Studying The Anti Candidal-Activity of Different Herbal Oils Incorporated into Tissue Conditioner: (A Comparative study) - Mohammed, Ghada Abdulmunim (Jordan Journal of Pharmaceutical Sciences, 2023)
This in vitro study was undertaken with the aim of testing the efficacy of the tissue conditioner mixed with four different commercially available herbal oils (Origanum oil, (Nigella sativa) Black seeds oil, Garlic oil, and Ginger oil) against Candida albicans. Control groups tested with antifungal test discs included fluconazole, flucytosine, and tissue conditioner discs (Acrosoft). The susceptibility test of plant extracts alone was also conducted. The combination groups tested were Acrosoft mixed with ginger oil, Acrosoft mixed with origanum oil, Acrosoft mixed with black seed oil, and Acrosoft with garlic oil. Test discs were completely embedded in the tissue conditioner mixed with plant extracts and gently placed on the agar plates. The plates were incubated at 35 °C for 72 hours. After incubation, inhibiting diameters of various groups were noted. There was complete resistance of Candida albicans to both fluconazole and flucytosine, and there was no inhibition zone observed regarding the susceptibility of ginger oil, origanum oil, black seed oil, and garlic oils. Similarly, there was no inhibition of Candida albicans observed in Acrosoft material. For the combination of tissue conditioner with plant extracts, results showed no inhibition in black seed oil and ginger oil combined with tissue conditioner. In contrast, the combination of garlic oil and origanum oil with tissue conditioner showed a zone of inhibition, and the inhibition diameters ranged from 5-9 mm.